Deep-Water Octocorals (Cnidaria, Anthozoa) from the Galápagos and Cocos Islands. Part 1: Suborder Calcaxonia - Cairns, Stephen D. (ZooKeys, 2018)
Thirteen species of deep-water calcaxonian octocorals belonging to the families Primnoidae, Chrysogorgiidae, and Isididae collected from off the Galápagos and Cocos Islands are described and figured. Seven of these species are described as new; nine of the 13 are not known outside the Galápagos region. Of the four species occurring elsewhere, two also occur in the eastern Pacific, one off Hawaii, and one from off Antarctica. A key to the 22 Indo-Pacific species of Callogorgia is provided to help distinguish those species.